Holocene aquatic ferns (Salviniaceae) from the eastern Chaco Region, Northeastern Argentina - Contreras, Silvina Andrea (2020)
The Chaco region is a large subtropical plain and one of the major biogeographic and morphostructural areas of South-America. Eastern Chaco is the wettest sector of the Chaco region and has heterogeneous environments. Vegetation results of Quaternary alluvial plain dynam-ics including the intensive migration of the Cha-co main rivers. Paleobotanical records do not attest significant floristic changes in the region during the last 10,000 years. Fern macrofossils (vegetative part impressions) and microfossils (spores) belonging to the group of heterosporous aquatic ferns (Salviniaceae) were collected from two sites (Formosa Province, Argentina) which include sediments of the Fidelidad Formation (Late Holocene - Bermejo River natural levees, Villa Escolar). Impressions correspond to Salvinia Ség. The floating leaves are orbicular to ellip-tical in shape, with smooth margin and both the apex as the base are rounded. The base bears a slightly developed keel. Venation pattern is di-chotomous. These veins are anastomosed forming areolas. Generally, four tubercles (trichome bases) per areola are observed. The microfos-sils correspond to massulae and spores of Azol-la Lam. The massulae are rounded, oval or kidney shaped and have septate glochidia. Spores are trilete and spheroidal. Aquatic ferns are sig-nificant paleoenvironmental indicators of open fresh water or wetlands, while Azolla and Salvin-ia represent floating plants. This evidence sug-gests that the basal sediments of the Fidelidad Formation formed under environments similar to those currently observed in the region.